Hypothyroidism and Sturge-Weber Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
Two children out of 83 (2.4%) with Sturge-Weber syndrome, who attended a multidisciplinary center at Johns Hopkins Hospital, Baltimore, MD, were found to have central hypothyroidism.